ANALISA DAN DESAIN SISTEM INFORMASI PEMASARAN PADA KEGIATAN UMKM BERBASIS KLASTER - Widiarti, Dian; Praja, Yudha (Growth, 2023)
Small and medium enterprises (MSMEs) are businesses that aim to provide economic services to consumers in order to generate income for the community and promote economic growth. In order to compete in today's tight business world, MSMEs need to innovate and adapt to the digital age. However, many MSMEs in Dawuhan Village face challenges such as limited product branding and market reach. The goal is to help MSMEs market their products more effectively and reach a wider audience. To address this issue, a marketing information system was developed using data from MSME owners in one cluster. The research involved surveying the initial conditions of MSME activities, analyzing system requirements, designing the system, and implementing it iteratively. The result is a design for a marketing information system that includes system requirements analysis, use case diagrams, sequence diagrams, database design, and website interface design.